2021
DOI: 10.3390/ijerph182212211
|View full text |Cite
|
Sign up to set email alerts
|

Critical Characteristics of Housing and Housing Supports for Individuals with Concurrent Traumatic Brain Injury and Mental Health and/or Substance Use Challenges: A Qualitative Study

Abstract: Traumatic brain injury (TBI) and mental health and/or substance use challenges (MHSU) are commonly co-occurring and prevalent in individuals experiencing homelessness; however, evidence suggests that systems of care are siloed and organized around clinical diagnoses. Research is needed to understand how housing and housing supports are provided to this complex and understudied group in the context of siloed service systems. This study aimed to describe critical characteristics of housing and housing supports f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The lack of training among service providers supporting individuals with TBI has been highlighted extensively in the literature, particularly among underserved populations ( 75 77 ), service users and families interacting with community services ( 80 ), in the context of TBI and mental health/substance use ( 81 ), and in some parts of the CJS ( 82 , 83 ). These studies also highlighted the importance of education in increasing TBI awareness and knowledge regarding appropriate supports and addressing negative views about TBI ( 82 , 84 ). Specific to the prison setting, educating staff on TBI and TBI-related behaviors and strategies to manage these behaviors could lead to decreased penalties and reduced negative interactions between staff and individuals with TBI in prison ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of training among service providers supporting individuals with TBI has been highlighted extensively in the literature, particularly among underserved populations ( 75 77 ), service users and families interacting with community services ( 80 ), in the context of TBI and mental health/substance use ( 81 ), and in some parts of the CJS ( 82 , 83 ). These studies also highlighted the importance of education in increasing TBI awareness and knowledge regarding appropriate supports and addressing negative views about TBI ( 82 , 84 ). Specific to the prison setting, educating staff on TBI and TBI-related behaviors and strategies to manage these behaviors could lead to decreased penalties and reduced negative interactions between staff and individuals with TBI in prison ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this scoping review highlights an opportunity to address the current fragmented care for individuals with TBI ( 80 , 84 , 86 88 ), including the lack of continuity in resources and support in community re-integration, ( 80 , 87 , 88 ) through Linkworker or NeuroResource Facilitator roles. These individuals provided direct support to the client while in custody and indirectly supported them by engaging health professionals, prison staff that interact with the client ( 52 – 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The view that TBI is a complex condition, and the need for, and importance of, formal TBI education and training has been identified in research outside of those included in this review. For example, a qualitative study sought the perspectives of housing services providers in Canada and identified attitudes around TBI that affected service delivery (72). Specifically, providers referred to TBI as an unknown and reported lacking TBI knowledge and expertise or needing to go "above and beyond" their role to support individuals with TBI in finding and maintaining housing (72).…”
Section: Considerations For Education and Training On Tbimentioning
confidence: 99%
“…Multidisciplinary teams may also facilitate opportunities for education on TBI. Alongside the call for formal education and training, housing service providers have also reported benefitting from partnerships and collaborations with healthcare professionals who had knowledge and expertise in working with individuals with TBI (72). This is particularly important given the intersecting challenges faced by individuals experiencing homelessness and TBI reported in articles included in this scoping review, including but not limited to criminal justice involvement (45,49,56,58,60,61) domestic violence (47), and comorbid mental health and substance use (MHSU) challenges (45,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Considerations For Education and Training On Tbimentioning
confidence: 99%